Language-Related Skills in Bilingual Children With Specific Learning Disorders - Anna Riva; Anna Riva; Alessandro Musetti; Monica Bomba; Monica Bomba; Lorenzo Milani; Lorenzo Milani; Valentina Montrasi; Renata Nacinovich; Renata Nacinovich (Frontiers in Psychology, 2021)
Purpose: The purpose of this study is to better understand the characteristics of the language-related skills of bilingual children with specific learning disorders (SLD). The aim is achieved by analyzing language-related skills in a sample of bilingual (Italian plus another language) and Italian monolingual children, with and without SLD.Patients and methods: A total of 72 minors aged between 9 and 11 were recruited and divided into four groups: 18 Italian monolingual children with SLD, 18 bilingual children with SLD, 18 Italian monolingual children without SLD, and 18 bilingual children without SLD. Each child underwent tests to evaluate different aspects of language skills: lexical and grammar, metalanguage and executive functions.Results: With regard to lexical and grammatical skills, the conditions of SLD and bilingualism both impact naming in terms of total number of errors for words with low frequency of use, while the condition of SLD has an effect on semantic errors for words with low frequency of use. The condition of bilingualism impacts on the total errors for words with high frequency of use and on circumlocution-type errors for words with low frequency of use. There were significant effects of bilingualism and SLD on the metalinguistic test for understanding implicit meaning, and an impact of SLD on phonological awareness was also found.Conclusion: The results suggest that both SLD and bilingualism have an effect on some lexical skills, in particular for words with low frequency of use. Both conditions, bilingualism and SLD, seem to impact on metalinguistic abilities that depend on lexical knowledge. These findings reinforce the importance of improving understanding of the neuropsychological profile of bilingual children with SLD.